Edukasi Prinsip Ergonomi Pada Postur Tubuh Saat Beraktivitas Untuk Mencegah Adanya Nyeri Punggung Bawah Di Puskesmas Banyuanyar - Helena Audrey Eldifa Khoirunnisa; Farid Rahman; Seliana Sinta Debi (Jurnal Pengabdian Masyarakat Nusantara, 2023)
Puskesmas Banyuanyar is a health facility located in Banjarsari District which has dua target areas, namely Banyuanyar Village and Sumber Village. With the boundaries of the Banyuanyar Puskesmas target area, in the north it is bordered by the working area of Boyolali Regency, in the south it is bordered by the working area of the Manahan Health Center, in the east it is bordered by the working area of the Gambirsari Health Center, and in the west it is bordered by the working area of Karanganyar Regency. Based on data from visits to the Banyuanyar Health Center physiotherapy poly, the incidence of Low Back Pain cases is found annually as many as 122 cases from 468 physiotherapy cases, this is caused by age, injury, and work factors. Pain is the main complaint that is often felt by patients in the condition of low back pain. The purpose of this program is to provide education and understanding on how to maintain low back health, prevention of low back pain and exercises that can be done at home. The method used is by providing counseling in the form of health promotion about low back pain and using leaflets as a medium of counseling, targeting the community who attend the Seruni RW 08 Sumber Elderly Posyandu. The author uses pre test and post test to determine the level of understanding of the people present. The results of the questionnaire showed an increase in participants' understanding as seen from the average pre-test score of 1.52, while the post test score obtained an average value of 8.43. This means that there is an increase in understanding of 6.91 from the average score of the questionnaire filled out by the community who attended the Seruni RW 08 Sumber Elderly Posyandu.